2021
DOI: 10.1007/s12325-021-01764-0
|View full text |Cite
|
Sign up to set email alerts
|

Systemic ALCL Treated in Routine Clinical Practice: Outcomes Following First-Line Chemotherapy from a Multicentre Cohort

Abstract: Introduction: Brentuximab vedotin (BV)-CHP is the new standard regimen for first-line treatment of systemic anaplastic large cell lymphoma (sALCL). We undertook a retrospective analysis of consecutive patients diagnosed with sALCL, treated in routine practice, to serve as a benchmark analysis for comparison BV-CHP efficacy in routine practice. Methods: Patients aged 16 years or older with sALCL treated in seven UK and Australian centres and from 14 additional centres from the UK Haematological Malignancy Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In 101 patients with sALCL in Japan, brentuximab vedotin treatment led to a 1-year OS of 79.3% and an ORR of 62.0% [ 55 ]. In 52 patients with sALCL who received brentuximab vedotin at relapse (primarily as second-line therapy), 3-year OS was 40.2% (median follow-up 34 months) [ 81 ]. In a retrospective study of brentuximab vedotin in combination with ICE for relapsed or refractory PTCL, 4 of 14 patients achieved an overall response and 2 achieved CR, with 2-year PFS and OS of 14% and 17.5%, respectively [ 82 ].…”
Section: Real-world Data On Brentuximab Vedotin In Ptclmentioning
confidence: 99%
“…In 101 patients with sALCL in Japan, brentuximab vedotin treatment led to a 1-year OS of 79.3% and an ORR of 62.0% [ 55 ]. In 52 patients with sALCL who received brentuximab vedotin at relapse (primarily as second-line therapy), 3-year OS was 40.2% (median follow-up 34 months) [ 81 ]. In a retrospective study of brentuximab vedotin in combination with ICE for relapsed or refractory PTCL, 4 of 14 patients achieved an overall response and 2 achieved CR, with 2-year PFS and OS of 14% and 17.5%, respectively [ 82 ].…”
Section: Real-world Data On Brentuximab Vedotin In Ptclmentioning
confidence: 99%
“…The International Peripheral T‐Cell Lymphoma Project reported five‐year progression‐free survival (PFS) of 60% and 36% for ALK‐positive and ALK‐negative sALCL, and five‐year overall survival (OS) of 70% and 49% respectively 6 . A recent large real‐world study of 214 patients treated with conventional chemotherapy reported a four‐year time to treatment failure of 28·2% and OS of 43·9% in ALK‐negative sALCL compared to 57·6% and 78·6% in ALK‐positive disease 7 …”
Section: Introductionmentioning
confidence: 99%
“…6 A recent large real-world study of 214 patients treated with conventional chemotherapy reported a four-year time to treatment failure of 28Á2% and OS of 43Á9% in ALKnegative sALCL compared to 57Á6% and 78Á6% in ALKpositive disease. 7 At relapse, chemoresistance to salvage chemotherapy limits the number of patients receiving consolidation with potentially curative autologous or allogeneic stem cell transplantation (SCT). 8,9 One large population-based cohort reported a median OS of just three months for both sALCL subtypes at relapse, 10 and therefore many centres employ autologous transplantation in first remission in an attempt to improve outcomes despite a lack of robust evidence supporting this approach.…”
Section: Introductionmentioning
confidence: 99%